2021
DOI: 10.4084/mjhid.2021.048
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of superior ophthalmic vein thrombosis and thrombocytopenia following ChAdOx1 nCoV-19 vaccine against SARS-CoV-2

Abstract: x

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“… 52 This section focuses on superior ophthalmic vein thrombosis, as reported in two isolated cases. 21 , 58 Both patients received the ChAdOx1 nCoV-19 vaccine. Panovska-Stavridis et al .…”
Section: Amnmentioning
confidence: 99%
See 1 more Smart Citation
“… 52 This section focuses on superior ophthalmic vein thrombosis, as reported in two isolated cases. 21 , 58 Both patients received the ChAdOx1 nCoV-19 vaccine. Panovska-Stavridis et al .…”
Section: Amnmentioning
confidence: 99%
“…Panovska-Stavridis et al . 58 describe a 29-year-old female who presented with severe headache, orbital swelling with proptosis, limited ocular motility, vertical diplopia, and reduced visual acuity 10 days after the first dose. Initial findings showed thrombocytopenia of 18 × 10 9 /L and high D-dimer levels of 35712 μg/L.…”
Section: Amnmentioning
confidence: 99%
“…Ultimately the patient was treated with anticoagulation and discharged. Elsewhere, Panovska-Stavridis et al reported on a case of a 29-year-old woman (Figure 1) who developed left orbital swelling, severe headache, and blurred left eye vision 10 days after receiving the AZD1222 vaccine [20]. MRI imaging demonstrated central filling defects and a diagnosis of superior ophthalmic vein thrombosis was made.…”
Section: Superior Ophthalmic Vein Thrombosismentioning
confidence: 99%
“…Bayas et al reported a case of bilateral superior ophthalmic vein thrombosis, ischemic stroke, and thrombocytopenia after ChAdOx1 nCoV-19 (AstraZeneca) vaccination, and other unilateral case reports have also been published. [105][106][107] Acute macular neuroretinopathy has been reported following the ChAdOx1 nCoV-19 vaccination, 108,109 and CNVI palsy has been reported 2 days after BNT162b2 mRNA vaccine (Pfizer), which resolved after 3 months. 110 Fan et al reported a case of branched retinal artery occlusion with features of paracentral acute middle maculopathy in a pediatric patient after BNT162b2 vaccination (personal communication).…”
Section: Potential Systemic and Ocular Side Effectsmentioning
confidence: 99%